2012
DOI: 10.1097/hjh.0b013e32834e5a4f
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of isolated home blood pressure monitoring for blood pressure control

Abstract: A protocol of HBPM without medication titration enhances the control of BP assessed by ABPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The remaining ten studies contained all three types of BP measurement (OBPM, HBPM, and ABPM) and BP control data. Two were cross-sectional observational analyses, 30 , 31 five were randomized controlled trials, 32 36 and three were quasi-experimental studies without an active intervention 37 , 38 or a control group. 39 The majority of study populations consisted of individuals with mild-to-moderate hypertension, either treated or untreated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining ten studies contained all three types of BP measurement (OBPM, HBPM, and ABPM) and BP control data. Two were cross-sectional observational analyses, 30 , 31 five were randomized controlled trials, 32 36 and three were quasi-experimental studies without an active intervention 37 , 38 or a control group. 39 The majority of study populations consisted of individuals with mild-to-moderate hypertension, either treated or untreated.…”
Section: Resultsmentioning
confidence: 99%
“… 33 Fuchs et al showed that merely randomizing an individual to HBPM and not making any antihypertensive medication adjustments improves BP control. 38 Using HBPM to titrate antihypertensive medication produces the same level of control as using ABPM. 36 …”
Section: Resultsmentioning
confidence: 99%
“…This cross-sectional study was done with patients screened to participate in the MONITOR study (Randomized clinical trial of efficacy of home blood pressure monitoring and target organ damage; ClinicalTrials.gov NCT00921791) [ 15 ]. This study was conducted in the Hypertension Clinic of the Division of Cardiology of Hospital de Clínicas de Porto Alegre (Porto Alegre, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria included severe hypertension (office BP ≥ 180/110 mmHg), secondary hypertension, disabling chronic disease (cancer, liver cirrhosis, heart failure, unstable angina pectoris, mental disorders), and myocardial infarction or stroke within six months of enrollment. The results of the main study were published elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Low- and middle-income countries may even be facing a persistent increase of individuals with high BP in the next decade [ 1 , 4 ]. Successful attempts have been shown to increase BP control [ 5 , 6 ] but have not been implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%